2018
DOI: 10.1159/000488200
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of F-18 FDG PET/CT for Preoperative Lymph Node Staging in Newly Diagnosed Bladder Cancer Patients: A Systematic Review and Meta-Analysis

Abstract: Aims: We aimed to assess the diagnostic accuracy of F-18 fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) for preoperative lymph node (LN) staging in newly diagnosed bladder cancer (BC) patients through a systematic review and meta-analysis. Patients and Methods: MEDLINE, Embase, and the Cochrane Library database, from the earliest available date of indexing through June 30, 2017, were searched for studies evaluating the diagnostic performance of F-18 FDG PET/CT for preoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 32 publications
0
25
1
2
Order By: Relevance
“…In a combined meta-analysis and single-institution study of patients with bladder cancer scheduled to undergo radical cystectomy and pelvic lymph node dissection, the authors determined that the pooled sensitivity and specificity for detection of lymph node metastases were 57% and 95%, respectively [52]. These findings were also confirmed in two subsequent meta-analyses, which demonstrated a pooled sensitivity of 56-57% and a pooled specificity of 92% for the detection of lymph node metastases on FDG-PET/CT [53,54]. A small (n = 15) study evaluating the use of FDG-PET/CT for the preoperative lymph node staging of MIBC demonstrated minimal benefit of FDG-PET/CT compared with CT alone, thought to potentially be due to overlap in standardized uptake values (SUVs) between inflammatory and malignant lesions [55].…”
Section: Fdg-pet/ct For Bladder Cancer Stagingmentioning
confidence: 85%
“…In a combined meta-analysis and single-institution study of patients with bladder cancer scheduled to undergo radical cystectomy and pelvic lymph node dissection, the authors determined that the pooled sensitivity and specificity for detection of lymph node metastases were 57% and 95%, respectively [52]. These findings were also confirmed in two subsequent meta-analyses, which demonstrated a pooled sensitivity of 56-57% and a pooled specificity of 92% for the detection of lymph node metastases on FDG-PET/CT [53,54]. A small (n = 15) study evaluating the use of FDG-PET/CT for the preoperative lymph node staging of MIBC demonstrated minimal benefit of FDG-PET/CT compared with CT alone, thought to potentially be due to overlap in standardized uptake values (SUVs) between inflammatory and malignant lesions [55].…”
Section: Fdg-pet/ct For Bladder Cancer Stagingmentioning
confidence: 85%
“…A recent meta-analysis including 14 studies and 785 patients reported that the pooled sensitivity and specificity of 18F-FDG PET/CT for initial pelvic LN staging, in a per patient analysis, were 57% [95% CI 49-64%] and 92% [95% CI 87-95%], respectively (19). One major limitation of the current literature is the heterogeneous methodologies across published studies, notably regarding study designs, inclusion criteria, administration of NAC, injection-acquisition time in PET, the use of forced diuresis, the administration of contrast media for PET/CT, and interpretation criteria for both CECT and PET/CT (20).…”
Section: Lymph Node Stagingmentioning
confidence: 99%
“…Several evidence-based articles were focused on the clinical usefulness of 18 F-FDG PET/CT in patients with bladder cancer [103][104][105][106][107][108][109]. An over-all sensitivity and specificity of 82% and 92% was reported, respectively [108].…”
Section: Bladder Cancermentioning
confidence: 99%
“…Sensitivity and specificity were 90% and 100%, respectively, for primary staging, and 82% and 89%, respectively, for restaging [105]. For detection of node metastases, specificity was found high, whereas sensitivity was poor [103,104,106]. Additionally, detection of node involvement was assessed by other radiopharmaceuticals such as 11 C-choline or 11 C-acetate [109], showing low sensitivity and moderate specificity.…”
Section: Bladder Cancermentioning
confidence: 99%